Disappointing outlook carrefour - Joosten, Marco (2022)
Founded in 1959, Carrefour is one of the leading French retailers listed on the Paris Stock Exchange. The company has over 60 years of experience in providing consumers across the globe a vast range of grocery products. Over the last decade, Carrefour has faced a changing market environment and declining financial returns, for which it has reconsidered its strategy. The company aims to leverage its omnichannel format and materialize the growth opportunities within the global retail sector, particularly E-Commerce. These opportunities develop continuously and four diverging future scenarios for the company are considered. A Sell recommendation as per 22 May 2020 is derived from these analyses.